Sociodemographic determinants of diet quality of the EU elderly : a comparative analysis in four countries - Irz, Xavier; Fratiglioni, Laura; Kuosmanen, Nataliya; Mazzocchi, Mario; Modugno, Lucia; Nocella, Giuseppe; Shakersain, Behnaz; Traill, Bruce W.; Xu, Weili; Zanello, Giacomo (Cambridge Journals, 2014)
Objective To investigate the sociodemographic determinants of diet quality of the elderly in four EU countries. Design Cross-sectional study. For each country, a regression was performed of a multidimensional index of dietary quality v. sociodemographic variables. Setting In Finland, Finnish Household Budget Survey (1998 and 2006); in Sweden, SNAC-K (2001–2004); in the UK, Expenditure & Food Survey (2006–07); in Italy, Multi-purpose Survey of Daily Life (2009). Subjects One- and two-person households of over-50s (Finland, n 2994; UK, n 4749); over-50 s living alone or in two-person households (Italy, n 7564); over-60 s (Sweden, n 2023). Results Diet quality among the EU elderly is both low on average and heterogeneous across individuals. The regression models explained a small but significant part of the observed heterogeneity in diet quality. Resource availability was associated with diet quality either negatively (Finland and UK) or in a non-linear or non-statistically significant manner (Italy and Sweden), as was the preference for food parameter. Education, not living alone and female gender were characteristics positively associated with diet quality with consistency across the four countries, unlike socio-professional status, age and seasonality. Regional differences within countries persisted even after controlling for the other sociodemographic variables. Conclusions Poor dietary choices among the EU elderly were not caused by insufficient resources and informational measures could be successful in promoting healthy eating for healthy ageing. On the other hand, food habits appeared largely set in the latter part of life, with age and retirement having little influence on the healthiness of dietary choices.
Keywords: ageing; diet quality; socio-economic; healthy eating; nutritional health; vanhukset; ravitsemus; elderly; diet; elderly nutrition; ikääntyneet; ruokavaliot; terveellisyys